Medial Patellofemoral Ligament Reconstruction and Lateral Retinacular Lengthening in the Skeletally Immature Patient - Levy, Benjamin J. (Arthrosc Tech, 2020)
Patellar instability remains a ubiquitous and troublesome problem in orthopaedics and represents a challenge in the pediatric population. Reconstruction of the medial patellofemoral ligament (MPFL) has become a mainstay of patellar instability management in recent years. As with any procedure at or around the physes, there is concern among surgeons regarding safe placement of hardware and drilled tunnels. The authors describe a technique for anatomic MPFL reconstruction with the aid of fluoroscopic guidance to maintain a “safe zone” without violating the distal femoral physis. This technique allows for reliable MPFL reconstruction in the skeletally immature population with concomitant lateral lengthening, while requiring only minor deviations from the procedure in a skeletally mature patient.